Welding consumables : gases and gas mixtures for fusion welding and allied processes (American Welding Society, 2011)
"This standard prescribes the requirement for the classification of gases and gas mixtures for fusion welding and allied processes. Classification is based on composition of the more popular single and multi-component gases. Additional requirements are included for purity and moisture of individual gas components, testing, retesting, packaging, and cylinder or container labeling. An annex is appended to the standard as a source of information concerning the classification system and the intended use of the gases and gas mixtures. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other."